'Digital soap opera' online radio listening patterns and the digital divide. Issue 2 (4th March 2017) - Moshe, Mira; Laor, Tal; Friedkin, Shimon
Abstract: This article examines the gendered digital divide in Israel in the age of the radiophonic cyber-revolution. The research focuses on increased listening patterns to on-demand, radiophonic content via online radio. Recent years have witnessed a shift in the second level of the gendered digital divide. This shift is effectively captured by the notion of 'can't' transforming into a 'don't want to be bothered' mindset. To explore this phenomenon an online survey was conducted on online listeners of a regional radio station. Israel's top-rated regional station, 103FM-Non-Stop Radio, was selected. The survey was conducted in April 2014. A total of 2013 listeners were surveyed: 1491 men and 522 women. Our results found that for the under 35 years of age listeners increased listening patterns were gender-blind. The same conclusion was reached for other demographic groups: The findings from this group do, in fact, attest to a gendered digital divide. The key demographic groups here are married couples and parents. These trends highlight the continued need for further research into online radio listening patterns and their relationship to gender-related differences in the digital age.